Digital Payments on the Agenda: How Supply-side Actors Framed Cash and Digital Payments during the COVID-19 Pandemic in India. Issue 2 (3rd April 2023) - Sam, Jillet Sarah; Ray, Rajorshi; Chakraborty, Anwesha
ABSTRACT: Debates about the increase in digital payments during COVID-19 have primarily focused on behavioural change among consumers. Using India as a case study, this article documents how supply-side actors (political, economic, financial and technological) used the pandemic to generate a new public consensus about digital payments. The article argues that these actors framed the agenda to draw public attention on cash and digital payments during the COVID-19 pandemic, that this new consensus extended and deviated from narratives created during the Digital India (2015) and demonetisation (2016) debates, and that trade bodies and businesses unrelated to banking, finance and technology were active in setting this new agenda. Agenda-setting in the pandemic era continues to mould the payments trajectory in both India and elsewhere. In India, we argue, it has challenged aspects of cash that previously elicited trust: its materiality and associated social interaction. Consequently, older agendas have been promoted, and digital (and especially contactless) payments have assumed a new level of importance to economic life in India.